2009
DOI: 10.1002/nur.20354
|View full text |Cite
|
Sign up to set email alerts
|

Data management for intervention effectiveness research: Comparing deductive and inductive approaches

Abstract: Management approaches are needed to prepare intervention data sets for research. We identified four management approaches and applied them to Omaha System intervention data from 15 home care agencies (621,385 interventions provided to 2,862 patients). Classifying intervention data created differing numbers of distinct groups for deductive approaches labeled as action category (four groups), theoretical (5), and clinical expert consensus (23). One inductive, data-driven approach generated 150 groups of interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Application of the data mining methods helped researchers to group co-occurring interventions inductively based on the existing data. After analyzing a large computerized dataset that included OS data on 2862 patients from 15 homecare agencies, Monsen et al 47 concluded that compared to the deductive approaches, the 'approach based on data mining generated more intervention groups that represented nursing care provided to complex homecare patients'. Afterwards, Monsen et al 28 used these intervention grouping approaches to explain hospitalization outcomes for frail and non-frail elders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of the data mining methods helped researchers to group co-occurring interventions inductively based on the existing data. After analyzing a large computerized dataset that included OS data on 2862 patients from 15 homecare agencies, Monsen et al 47 concluded that compared to the deductive approaches, the 'approach based on data mining generated more intervention groups that represented nursing care provided to complex homecare patients'. Afterwards, Monsen et al 28 used these intervention grouping approaches to explain hospitalization outcomes for frail and non-frail elders.…”
Section: Discussionmentioning
confidence: 99%
“…For example, even though there is evidence of application of the OS in clinical settings other than community and public health, 72 this review identified only one publication 53 describing OS data in acute care settings. This lacking evidence is critical to further Analyze clinical process 5 [22][23][24][25][26] Analyze client outcomes 16 9 27-41 Advance classification research 12 [42][43][44][45][46][47][48][49][50][51][52][53] Other 16 10 54-68 advance the meaningful use of standardized terminologies. Furthermore, the most recent report by the National Academies of Science and Agency for Healthcare Research and Quality 73 suggested ways to improve care provided in people's homes by formal and informal caregivers (such as family members).…”
Section: Discussionmentioning
confidence: 99%
“…There are 12,600 possible combinations of problem, category, and target terms, each of which can be further customized using the care description. These interventions have been successfully employed to discover new health care knowledge using complex statistical models and data mining methods [13][14][15].…”
Section: The Omaha Systemmentioning
confidence: 99%
“…There are 12,600 possible combinations of problem, category, and target terms, each of which can be further customized using the care description. These interventions have been successfully employed to discover new health care knowledge using complex statistical models and data mining methods [13][14][15].Concept duplication is considered a threat to the validity of a structured interface terminology [5]. In an early edition of the Omaha System, 2 concepts (nutrition, substance use) were exactly duplicated as terms at the problem and target levels [16].…”
mentioning
confidence: 99%
“…New clinical data sets that provide essential health assessment and service data are becoming available, and methods for meaningful use of the data are emerging [7][8][9]. Interface terminologies enable documentation of clinical assessments and services within the electronic health record.…”
Section: Introductionmentioning
confidence: 99%